Penilaian Tingkat Kepuasan Layanan Produk/Jasa dengan Metode Service Quality Model - Almantara, I Putu Sugi; Sudarma, Made; Swamardika, Ida Bagus Alit (Majalah Ilmiah Teknologi Elektro; Vol 20 No 2 (2021): (Juli-Desember) Majalah Ilmiah Teknologi Elektro, 2021)
Product / service satisfaction is one of several factors that can influence a company. Satisfaction is something that can be measured to improve and achieve goals in a company / government institution. The level of satisfaction can be measured by utilizing several methods, including Service Quality. Service Quality can show the difference between the customer's expectations of the company and the services received by the customer and the difference between the expectations and the services received can be seen the level of satisfaction provided by the customer. This study aims to determine the application of the Service Quality method in measuring the level of product / service satisfaction at companies or government institutions with the concept of literature review. The results of the literature review show that the application of the Service Quality method is more widely used in private companies than government institutions. The results also show that product / service service satisfaction is better at government institutions compared to private companies. This is shown in one of the literature which resulted in the achievement of very good levels of satisfaction with service quality in government institutions.